Parcerias estratégicas entre propriedades rurais para a geração de bioenergia - Barbosa, Gabriela Diedrichs (2018)
The agricultural sector generates a lot of residues. These residues are a serious environmental problem when they are not properly disposed or reused. The search for sustainability in this sector and the problems associated with the energy crisis and global warming encourage the use of agricultural waste as an energy source. However, the installation of a plant for the generation of bioenergy requires high investments and volume of waste. These are stimuli for cooperation between rural producers. In Brazil, the joint generation of energy through renewable sources is authorized by the National Electric Energy Agency. In this sense, the objective of this work was to identify alternatives of strategic partnerships between rural properties for the generation of bioenergy. The study was carried out on cattle and/or pigs farms, associated to an agroindustrial cooperative, located in the municipality of Castro-Paraná-Brazil. The methodology was based on the creation of a partnership scenario. The variables energy consumption, bioenergy generation potential and geographic location of rural properties were taken into account. The bioenergy generation potential was calculated by means of a mean between the indices obtained in the literature. The Elbow method defined the optimal number of clusters. The partnership scenarios were created by the k-means algorithm, using the QGIS geoprocessing software and the SPSS statistical software. Three scenarios of partnerships between rural properties were obtained. The overlap of the scenarios generated a final scenario of partnerships, composed of three groups. The group 1 has the potential to meet 36% of its energy demand; the group 2 has the potential to meet 32% of its energy demand; and, finally, the group 3 has the potential to meet 72% of its energy demand. The methodology developed in this work made it possible to find alternative partnerships for the generation of bioenergy among the rural properties studied. This methodology can be applied in other samples. The joint production of bioenergy contributes to the sustainability and energy security of the rural sector.